P‐Si/SnO2/Fe2O3 Core/Shell/Shell Nanowire Photocathodes for Neutral pH Water Splitting. (21st March 2015) - Kargar, Alireza; Kim, Sung Joo; Allameh, Paniz; Choi, Chulmin; Park, Namseok; Jeong, Huisu; Pak, Yusin; Jung, Gun Young; Pan, Xiaoqing; Wang, Deli; Jin, Sungho
<x xml:space="preserve">Abstract</x> Silicon is one of the promising materials for solar water splitting and hydrogen production; however, it suffers from two key factors, including the large external potential required to drive water splitting reactions at its surface and its instability in the electrolyte. In this study, a successful fabrication of novel p‐Si/n‐SnO2/n‐Fe2O3 core/shell/shell nanowire (css‐NW) arrays, consisting of vertical Si NW cores coated with a thin SnO2 layer and a dense Fe2O3 nanocrystals (NCs) shell, and their application for significantly enhanced solar water reduction in a neutral medium is reported. The p‐Si/n‐SnO2/n‐Fe2O3 css‐NW structure is characterized in detail using scanning, transmission, and scanning transmission electron microscopes. The p‐Si/n‐SnO2/n‐Fe2O3 css‐NWs show considerably improved photocathodic performances, including higher photocurrent and lower photocathodic turn‐on potential, compared to the bare p‐Si NWs or p‐Si/n‐SnO2 core/shell NWs (cs‐NWs), due to increased optical absorption, enhanced charge separation, and improved gas evolution. As a result, photoactivity at 0 V versus reversible hydrogen electrode and a low onset potential in the neutral solution are achieved. Moreover, p‐Si/n‐SnO2/n‐Fe2O3 css‐NWs exhibit long‐term photoelectrochemical stability due to the Fe2O3 NCs shell well protection. These results reveal promising css‐NW photoelectrodes from cost‐effective materials by facile fabrication with simultaneously improved photocathodic performance and stability.